[Harold Miossi and two others on hiking path]
Harold Miossi and unidentified woman and child walk down a hiking path located near the Cuesta Grade. At the forefront is Miossi's Dalmatian, Galore. A ridge rises behind them in the background. A trees is located to the right of Harold Miossi.